Teaching English for Specific Purposes in Vocational High School: Teachers’ Beliefs and Practices - Muliyah, Pipit; Aminatun, Dyah (JET (Journal of English Teaching), 2020)
This study reports the result of a qualitative case study research design. This study aims to explore teachers' beliefs about teaching English for Vocational school, to investigate how those beliefs are reflected in classroom practices, and to explore that affect the shaping of teachers' beliefs in the teaching and learning process. The participant of this study were six English teachers from three different vocational high schools in Majenang. The data was taken using a semi-structured interview, documentation, and classroom observation. Then the data was analyzed using line by line analysis. Teaching English in Vocational High School is believed different from Senior High school (SHS) as it belongs to English for specific purposes (ESP) and demands different knowledge of material, method, and strategies. The result shows that the teacher’s beliefs are not always realized in their classroom practices for a variety of potential reasons. The inconsistency between belief and practices are related to various factors, including class density, time constrains, incompatibility of the assigned text-books, huge workload, and students need.